USE OF ELEMENTS OF 3D PRINTING IN MEN'S SUIT DESIGN - BABYCH, Antonina; KERNESH, Viktoriia; TKACHENKO, Daniil (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The use of innovative methods and constructive solutions, non-typical textural and structural materials and elements of 3 printing in the development of the design of models of products of the fashion industry, and in particular clothes, attracts the attention of fashion industry specialists, starting from interesting and creative ideas, creating collages of inspiration, performing quick black and white sketches of products, selection of materials and components, as well as in the detailed development of elements of men's suit constructions. Development of an assortment of modern and creative men's suits from various non-typical materials and elements for the industry is a bold challenge of the designer to society, his idea, vision of the world of emotions, fashion and beauty. This is partly an opportunity to save natural resources and use as decorative elements of the suit 3 printing details imitating metal chains. The article investigates and analyzes the relevance and technological possibility of using 3D printing elements in the form of chains of various weaves for the design of a collection of men's suits for industrial and individual collections.The issue of fashion trends in the design of men's suits has been studied and analyzed. An analysis of world brands of clothing manufacturers was conducted, the theoretical feasibility of this development was proved. The results of theoretical and analytical research on the possibility of using bold constructive ideas and solutions in men's suits are presented. Developed a sketch project, 3D models of chains, made with the help of a 3D printer "Prusa" chain samples for use in the men's suit collection. Samples-modules of products were made in the material for visualization of the idea. This development was presented at the startup competition of works of young designers, Kyiv KNUTD (2022). The feasibility of this development has been proven theoretically. The collection of products will be presented at the competition "Cave Chestnuts", Kyiv.
Keywords: suit; color; shape; construction; manufacturability of the model; 3D model; fashion; innovation; demand; product